Relationship of environment with technological innovation, carbon pricing, renewable energy, and global food production. Issue 8 (17th November 2021) - Anser, Muhammad Khalid; Khan, Muhammad Azhar; Nassani, Abdelmohsen A.; Aldakhil, Abdullah Mohammed; Hinh Voo, Xuan; Zaman, Khalid
ABSTRACT: The United Nation sustainable development goals are largely emphasized on advancement in cleaner production technologies to take action against climate change and maintain the average global temperature less than 1.5°C. The role of carbon pricing, renewable energy, and sustainable food production would be helpful to achieve sustainable development goals in line with technological innovations. This study works in given factors and evaluated the global pace of economic growth towards sustainable development. The ex-ante and ex-post analysis is carried out on the world aggregated data for a period of 1980–2017. The results show that knowledge spillover, combustible renewables & waste, and carbon pricing substantially decreases carbon emissions, whereas trademark applications have a direct relationship with carbon emissions that exhibit the innovation embodied emissions at a global scale. The results support the inverted U-shaped relationship between carbon emissions and global income with a turning point of US$15, 800 and US$11, 100 by using FMOLS and DOLS estimators respectively. The ex-ante analysis shows that knowledge spillover, trademark applications, and carbon pricing will largely decrease carbon emissions while carbon pricing, food production index, FDI inflows, and broad money supply will decrease fossil fuel emissions for the next 10 years time period.